ANALISIS PENDAPATAN PETANI KELAPA DI DESA RANOKETANG ATAS KECAMATAN TOULUAAN KABUPATEN MINAHASA TENGGARA (Income Analysis of Coconut Farmers in Ranoketang Atas Village, Touluaan Sub District, Southeast Minahasa Regency) - Marton Eric Datu; Eyverson Ruauw; Noortje M. Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to analyze income, income comparison and the feasibility of coconut farming, both those selling in the form of coconut seeds and those selling in the form of copra in Ranoketang Atas Village, Touluaan District, Southeast Minahasa Regency. Data collection methods are interviews, recording and documentation. The data collected in this study are primary data obtained from direct interviews with respondents through questionnaires and secondary data obtained from the Ranoketang Atas Village office and Touluaan Sub District Office. The research results indicated that there is a significant difference level of income between farmers who sell coconuts in the form of coconut seeds and farmers who sell coconuts in the form of copra with the average income of farmers who sell coconuts in the form of coconut seeds of Rp. 16,915,929 per quarter and the average income of farmers who sell coconut in the form of copra is Rp. 20,719,939 per quarter. The results of the feasibility analysis of farming obtained a value of more than 1 which means that coconut farming run by coconut farmers in the village of Ranoketang Atas, Touluaan Sub District, Southeast Minahasa Regency is feasible.